An electrical vortex air‐assisted spraying system for improving droplet deposition on rice. Issue 10 (22nd June 2022) - Qiu, Wei; Guo, Hongbin; Cao, Yubin; Li, Xiaolong; Wu, Jianhao; Chen, Yunfu; Yu, Hongfeng; Zhang, Zhengwei
Abstract: Background: To improve droplet deposition rates at the base of rice, an electrical vortex air‐assisted spraying system for small‐ and medium‐sized high‐clearance boom sprayers was developed. This system uses vortex airflows to guide droplets to the base of rice and the back of leaves, as well as to increase leaf perturbation and droplet penetration and deposition. Results: The spatial distribution of the airflow field generated by this system and the effects of the canopy on the airflow field were described. An orthogonal experiment was performed in a rice field based on fan speed, auxiliary airflow angle, and spray height as the experimental factors. It was discovered that a fan speed of 4000 rpm, auxiliary airflow angle of 0°, and spray height of 30 cm were optimal for droplet deposition at the base of the canopy. These settings resulted in droplet coverage of 54.5% and 35.9% on the front and back of the leaves, respectively, which are 48% and 104% higher than that on the front and back sides of leaves without an auxiliary airflow, respectively. Conclusion: Compared with the traditional application method, vortex air‐assisted application significantly improved the rate of droplet coverage in rice canopy of different area. Hence, vortex air‐assisted application enables new approaches and methods for rice crop protection. © 2022 Society of Chemical Industry. Abstract : Vortex air‐assisted application significantly improved the rate and uniformity of droplet coverage within the canopy of the rice plant.